Gut Bacteria-Based Cancer Therapy and Anti-Solid Tumor Mechanisms - Tianzhu Zhang; Xiao-Mei Yu; Shang-Tian Yang; Wen-Wen Zhou (Microbiology Research)
Cancer constitutes a significant global health challenge, ranking among the leading contributors to worldwide mortality. The inherent limitations of conventional oncologic interventions, particularly their frequent inability to induce durable remissions in advanced malignancies, continue to drive transformative explorations into novel therapeutic paradigms. In recent years, bacteria-based therapies have gained recognition in the management of solid tumors. Compared to traditional therapeutic modalities, extensive research has demonstrated that bacteria possess remarkable anticancer properties. Gut bacteria, which naturally coexist within the human body, represent a unique category of living cells with inherent advantages for solid tumor treatment. These microorganisms are characterized by their relative safety, ease of cultivation, and potential for use in precision medicine through genetic modifications. Furthermore, gut bacteria exhibit diverse mechanisms of action against tumor cells, with different bacterial species potentially exerting synergistic effects. However, the precise anticancer mechanisms of these bacteria, particularly those of gut microbiota, require further detailed investigation. This review categorizes anticancer gut bacteria according to their effects on cancer cells and elucidates their anticancer mechanisms across five domains: modification of the tumor microenvironment, competitive inhibition, activation of immune cells, vectors for gene therapy, and production of bacterial anticancer biomolecules. Additionally, we discuss the potential challenges of utilizing different gut bacteria for cancer treatment, highlight their anticancer advantages, and suggest promising directions for future research. Ultimately, this review serves as a comprehensive guide for utilizing both natural and engineered gut bacteria as therapeutic agents against solid tumors in cancer treatment.